1974
DOI: 10.1177/109019817400200202
|View full text |Cite
|
Sign up to set email alerts
|

Delay in the Detection of Cancer: A Review of the Literature

Abstract: University of the Negev , Beersheba THE EXISTING KNOWLEDGE ABOUT DELAY The Consequences of DelayIt would be easy to compile an impressive list of quotations testifying to the importance of cutting down the delay which precedes therapeutic action for cancer patients. Dominant professional opinion tends to coincide with common sense in arguing that the earlier the patient gets to the therapist, the more likely is his life to be saved. Thus, for example, Wiggins et al '°' estimated that the overall five-year canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(19 citation statements)
references
References 66 publications
2
16
0
1
Order By: Relevance
“…Normalization was the predominant causal attribution, which is consistent with findings of attribution studies in RA. (16)(17)(18) as well as other diseases (6,19,20). Subject responses or actions related to initial symptoms were consistent with the meaning attached to symptoms.…”
Section: Resultssupporting
confidence: 60%
“…Normalization was the predominant causal attribution, which is consistent with findings of attribution studies in RA. (16)(17)(18) as well as other diseases (6,19,20). Subject responses or actions related to initial symptoms were consistent with the meaning attached to symptoms.…”
Section: Resultssupporting
confidence: 60%
“…Presumably, knowledge about oral cancer aids more accurate symptom interpretation and the decision to seek help. Although it is recognized that knowledge alone may not be sufficient [as presumably knowledge interacts with affective reactions, conceptualizations of cancer, and other factors (42, 43)], the association between knowledge and patient delay has implications for information provision about cancer to those at risk of developing the disease. Promisingly, a leaflet has been shown to increase knowledge of oral cancer and intention to agree to an oral cancer screen (44).…”
Section: Discussionmentioning
confidence: 99%
“…In order to reach the persons who could benefit from genetic information, public information and education is crucial. Prior experience with public education and information [3] indicates that knowledge about "cancer symptoms" is a necessary, but not sufficient factor in seeking help, and that the way persons deal with such information is influenced by a variety of psychosocial variables. We also know from experience with Huntington's disease that prior to the possibility of genetic testing 75% of persons at risk indicated that they would be interested in such a test, but only 20% have requested a test after it has been established [4].…”
Section: General Psychological Aspects Of Genetic Detectionmentioning
confidence: 99%